A Pole, a Jew, a Mother, a Communist: Tonia Lechtman's Biography between Home and Exile. Issue 1 (February 2023) - Müller, Anna
In this article, using the example of Tonia Lechtman, a Polish Jew, a Communist, and a mother, I look at the process of identity shifting. Throughout her life, Tonia Lechtman lived in multiple countries—Poland (1918–1935), Palestine (1935–1937), France (1937–1942), Switzerland (1942–1946), Poland (1946–1971), and Israel (1971–1996)—and in most of those places, she lived on the margins of society while either committed to working for the cause she believed in, Communism, or trying to create a safe space for her small children. The article looks at how her understanding of her own Jewishness and Polishness shifted while Poland remained a place that served as a model home, a project to complete while transforming it into a space of safety and personal growth. At the same time, Communism remained an idea, but also her social reality that framed the space for her shifting identities. The complexity of the intersections of these various roles and identities—their fluidity, on the one hand, and determinacy, on the other—defined how she experienced her life.